Write the quadratic equation in general form and then choose the value of "b."
(2x - 1)(x + 5) = 0

(2x - 1)(x + 5) = 0 2x^2 + 10x - x - 5 = 0 2x^2 + 9x - 5 = 0 The value of b is 9.

Question

Asked 7/18/2013 8:56:07 AM

Updated 5/21/2015 6:19:20 AM

1 Answer/Comment

Edited by Andrew. [5/21/2015 6:18:04 AM]

Rating

3

(2x - 1)(x + 5) = 0

2x^2 + 10x - x - 5 = 0

2x^2 + 9x - 5 = 0

The value of b is 9.

2x^2 + 10x - x - 5 = 0

2x^2 + 9x - 5 = 0

The value of b is 9.

Added 5/21/2015 6:19:20 AM

This answer has been confirmed as correct and helpful.

(4ab - 8a^2 + 12ac) ÷ 4a

Question

Expert Answered

Updated 9/30/2016 3:07:36 PM

1 Answer/Comment

(4ab - 8a^2 + 12ac) ÷ 4a

= (4ab/4a) + (-8a^2/4a) + (12ac/4a)

= -2a + b + 3c

= (4ab/4a) + (-8a^2/4a) + (12ac/4a)

= -2a + b + 3c

Added 9/30/2016 3:07:19 PM

This answer has been confirmed as correct and helpful.

(3x^2 + 2x - 3)(x - 1)
3x2+ 3x- 4
3x3- 5x2- 5x+ 3
3x3-x2- 5x+ 3
3x3+ 5x2- 5x+ 3 **Weegy:** (3x^2 + 2x - 3)(x - 1)= 3x^3 - x^2 - 5x + 3 (More)

Question

Expert Answered

Updated 3/8/2014 1:12:38 PM

0 Answers/Comments

3(2y - 8) - 2y(5 - y)
-2y2+ 16y - 24
-5y - 8
2y2- 4y - 24
2y2+ 16y - 24

Question

Not Answered

Updated 172 days ago|5/25/2018 10:45:08 AM

2 Answers/Comments

[Deleted]

Added 172 days ago|5/25/2018 10:44:41 AM

This answer has been added to the Weegy Knowledgebase

Deleted by jeifunk [5/25/2018 10:44:47 AM]

3(2y - 8) - 2y(5 - y)

= (3)(2y) + (3)(-8) + 2y^2 + (-10y)

=6y+ (-24) + 2y^2 + (-10y)

=(2y^2) + (6y + (-10y)) + (-24)

=2y^2 - 4y - 24

= (3)(2y) + (3)(-8) + 2y^2 + (-10y)

=6y+ (-24) + 2y^2 + (-10y)

=(2y^2) + (6y + (-10y)) + (-24)

=2y^2 - 4y - 24

Added 172 days ago|5/25/2018 10:45:08 AM

This answer has been confirmed as correct and helpful.

Making predictions based on hints or clues within the story, such as Odysseus talking about the wine Maron gave him, is known as ______ .
symbolism
motifs
theme
foreshadowing
plot

Question

Not Answered

Updated 11/25/2015 5:09:24 PM

1 Answer/Comment

Simplify.
x8 ÷ x4 · x2

Question

Expert Answered

Updated 5/10/2015 5:26:24 AM

1 Answer/Comment

x^8 ÷ x^4 · x^2

= x^4*x^2

= x^6

= x^4*x^2

= x^6

Added 5/10/2015 5:01:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/10/2015 5:26:16 AM]

27,651,955

questions answered

There are no comments.